Analisis Strategi Kesuksesan BMT Barrah dalam Upaya Pengembangan UMKM - Lovakri, Ulul Fatha; Saepurrohman, Muhammad (Ikatan Da'i Indonesia, 2024)
Micro enterprise is a form of small enterprise that is the implementation of the concept of the people's economy. As an important economic player in Indonesia, UMKM has the ability to attract labour from the majority of the population and increase their incomes evenly. Micro, small, and medium-sized (SMEs) continue to grow, but still face financial management problems, namely the difference between private capital and corporate money. The purpose of this research is to analyze BMT Barrah strategy in the effort to develop UMKM. The method of research used is qualitative research with a descriptive approach. The data used in this research is qualitative data that is data presented in the form of a sentence or writing not numbers. The results of this research are the strategy carried out by BMT Barrah in efforts to develop UMKM with support and supervision.